Sound Attenuation in Quark Matter Due to Pairing Fluctuations - Kerbikov, Boris (EPJ Web of conferences, 2016)
The sound wave in dense quark matter is subject to strong absorption due to diquark field fluctuations above Tc. The result is another facet of Mandelshtam-Leontovich slow relaxation time theory.